A decoupled flexure-based rotary micropositioning stage with compact size. (November 2018) - Zhu, Xiaobo; Wen, Zhijie; Chen, Guozhen; Liang, Jiaxin; Liu, Pinkuan
This paper presents the design and analysis of a novel compact flexure-based rotary micropositioning stage driven by piezoelectric actuator. The developed stage possesses a double four-bar rotary mechanism with rotational symmetric configuration and totally kinematic decoupling, which can convert the linear motion of the piezoelectric actuator into the pure rotational motion, significantly minimizing the parasitic error at the rotation center. Based on the configuration, a single piezoelectric actuator is employed to drive the stage, avoiding actuator redundancy and large configuration size. Meanwhile, we introduce a compliant rotational guiding mechanism to enhance the rotational stiffness and dynamics of the stage. Analytical modeling and finite element analysis are adopted to facilitate the design of dimension. Finally, a prototype of the stage is manufactured and tested, which is capable of a rotational angle of1 . 58 mrad with the first natural frequency of 430 Hz, whilst the well-constrained maximum center shift along the X - and Y -axis are 0.29 µm and 0.12 µm, respectively, indicating good decoupling capability. Furthermore, the compact size of70 mm × 70 mm × 15 mm is beneficial for limited working space.